2010
DOI: 10.1074/jbc.m109.081521
|View full text |Cite
|
Sign up to set email alerts
|

Rab8 Interacts with Distinct Motifs in α2B- and β2-Adrenergic Receptors and Differentially Modulates Their Transport

Abstract: The molecular mechanism underlying the post-Golgi transport of G protein-coupled receptors (GPCRs) remains poorly understood. Here we determine the role of Rab8 GTPase, which modulates vesicular protein transport between the trans-Golgi network (TGN) and the plasma membrane, in the cell surface targeting of ␣ 2B -and ␤ 2 -adrenergic receptors (AR). Transient expression of GDP-and GTP-bound Rab8 mutants and short hairpin RNA-mediated knockdown of Rab8 more potently inhibited the cell surface expression of ␣ 2B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 55 publications
4
83
0
Order By: Relevance
“…Whereas the molecular mechanisms governing the forward transport of GPCRs are still less well understood when compared with the extensive studies on their ligand-induced endocytic pathways, emerging evidence suggest that ER-toGolgi and post-Golgi trafficking of GPCRs are the highly regulated processes that involve specific conserved sorting motifs and regulatory proteins (1,45,46). Our results demonstrate that phosphorylation and subsequent 14-3-3 binding critically promote the surface expression of GPR15 (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Whereas the molecular mechanisms governing the forward transport of GPCRs are still less well understood when compared with the extensive studies on their ligand-induced endocytic pathways, emerging evidence suggest that ER-toGolgi and post-Golgi trafficking of GPCRs are the highly regulated processes that involve specific conserved sorting motifs and regulatory proteins (1,45,46). Our results demonstrate that phosphorylation and subsequent 14-3-3 binding critically promote the surface expression of GPR15 (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Glutathione S-transferase (GST) fusion protein constructs coding the ␣ 2B -AR CT were generated in the pGEX-4T-1 vector as described previously (19). All mutants were made with the QuickChange site-directed mutagenesis kit.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, the small GTPases Rab1, Rab6, Rab8, and Sar1 are able to selectively or differentially modulate the cell surface transport of GPCRs, suggesting that distinct GPCRs with similar structural features may use different pathways to move to the cell surface en route from the ER and the Golgi (14 -21). More recently, we have demonstrated that Rab8 and ARF1 directly interact with the receptors to modulate receptor cell surface transport (18,19).…”
mentioning
confidence: 99%
“…2 During the last decade, many studies described the involvement of Rab GTPases in the regulation of GPCR trafficking and signaling. Rab GTPases were shown to be key regulators of GPCR anterograde and retrograde transport (Rab1, Rab2, Rab6, and Rab8), [3][4][5][6] endocytosis (Rab5), [7][8][9][10][11] recycling (Rab4 and Rab11), [11][12][13][14][15][16][17][18][19] and degradation (Rab7). 20 We and others established that a direct interaction between a GPCR and a Rab GTPase appears to be necessary in the proper trafficking of the receptor.…”
Section: Gpcrs and The Regulation Of Rab Gtpasesmentioning
confidence: 99%